Quantification of creep stresses within HAZ in welded branch junctions. Issue 1 (30th June 2014) - Han, J.‐J.; Kim, Y.‐J.; Jerng, D. W.; Nikbin, K.; Dean, D.
ABSTRACT This paper quantifies the mismatch effect in creep properties on creep stresses in the heat‐affected zone of welded branches using systematic elastic‐creep finite element analysis. It is found that the section‐averaged normalized stresses in the heat‐affected zone can be uniquely characterized by the mismatch factor in creep. The relationship is almost linear and is not so sensitive to the loading condition. Implication to practical creep life assessment of welded branch components is discussed in the context of the R5 procedure.